STUDENTS’ PERSPECTIVE ON HYBRID LEARNING AFTER THE COVID-19 BREAK : A LEARNING REFLECTION THROUGH PHOTOVOICE - Diah Safithri Armin; Ayu Meita Puteri Siregar (UIN Sumatera Utara Medan, 2022)
After the COVID-19 pandemic hit, the world of education, including universities, had to find a solution on how education could continue to run well. During the pandemic, lectures are conducted online. However, after the conditions improved, the lectures were shifted to hybrid learning. The aim of this study was as a self-reflection through the experiences and perspectives of EFL students regarding the application of hybrid learning as an adjustment to the COVID-19 pandemic. This study uses photo voice as a research methodology involving 5 EFL students from 4 different classes. The results showed that, according to participants, hybrid learning was not the right solution for lectures for one semester. Internet disturbances and the unpreparedness of lecturers in implementing hybrid learning are the causes.